Early arterial access for resuscitative endovascular balloon occlusion of the aorta is related to survival outcome in trauma. Issue 3 (September 2018) - Matsumura, Yosuke; Matsumoto, Junichi; Kondo, Hiroshi; Idoguchi, Koji; Ishida, Tokiya; Okada, Yohei; Kon, Yuri; Oka, Kazuyuki; Ishida, Kenichiro; Toyoda, Yukitoshi; Funabiki, Tomohiro
Abstract : BACKGROUND: Resuscitative endovascular balloon occlusion of the aorta (REBOA) has been used in refractory hemorrhagic shock patients. Since the optimal timing of arterial access remains unclear, we evaluated the preocclusion status of patients, and elapsed time from the arrival to the hospital is associated with the survival outcomes in the REBOA patients. METHODS: From August 2011 to December 2016, The Diagnostic and Interventional Radiology in Emergency, Critical care and Trauma-Intra-Aortic Balloon Occlusion (DIRECT-IABO) investigators registered refractory hemorrhagic shock patients undergoing REBOA from 23 hospitals in Japan. Patient characteristics, mechanism of injury, Injury Severity Score (ISS), preocclusion and postocclusion systolic blood pressure, duration of aortic occlusion, clinical time course, and survival outcome were recorded and analyzed. Binary logistic regression analysis was used with mortality and Kaplan-Meier survival analysis was conducted to demonstrate the difference between early and delayed access groups. RESULTS: Among the enrolled 207 cases, the following patients were excluded from the analysis: five since they were younger than 18 years, nine due to failed attempts at REBOA, 51 nontrauma patients, and 33 who received resuscitative thoracotomy plus REBOA. Thus, the remaining 109 cases were analyzed (30-day survivors, n = 60; nonsurvivors, n = 49). The preocclusion systolic blood pressure was higher, and both hospital arrival to initial arterial access and duration of occlusion were shorter in the survivors. Lower ISS (odds ratio, 0.944; 95% confidence interval, 0.907–0.982; p = 0.0039) and shorter arrival to access (odds ratio, 0.989; 95% confidence interval, 0.979–0.999; p = 0.034) were significantly associated with 30-day survival in the logistic regression analysis. The cutoff point of 21.5 minutes was used in the receiver operating characteristic analysis. The early access group showed a significantly shorter time of arrival to definitive hemostasis and also demonstrated a significantly higher survival in the Kaplan-Meier survival analysis ( p = 0.014, Log-rank test). CONCLUSION: The arrival to access time and ISS were significantly associated with mortality in the REBOA patients in Japan. The early access group demonstrated better survival. The proactive early access in the resuscitation phase might be related to better patient outcomes. LEVEL OF EVIDENCE: Therapeutic/care management, level V.